2013
DOI: 10.1002/wrcr.20124
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varying sensitivity analysis clarifies the effects of watershed model formulation on model behavior

Abstract: [1] Lumped rainfall-runoff models are widely used for flow prediction, but a longrecognized need exists for diagnostic tools to determine whether the process-level behavior of a model aligns with the expectations inherent in its formulation. To this end, we develop a comprehensive exploration of dominant parameters in the Hymod, HBV, and Sacramento Soil Moisture Accounting (SAC-SMA) model structures. Model controls are isolated using time-varying Sobol 0 sensitivity analysis for twelve MOPEX watersheds in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 91 publications
3
141
0
Order By: Relevance
“…The contribution of interactions is larger for middle-magnitude flows than for small and large discharges. The different contributions of interactions for various magnitude flows may be because different magnitude rainfall data could trigger different hydrological processes (Herman et al, 2013). Small discharges mainly come from base flows which are relatively stable and do not need much rainfall to be triggered, and large discharges are mainly controlled by overland flows when heavy precipitation occurs.…”
Section: Uncertainty Source Quantificationmentioning
confidence: 99%
“…The contribution of interactions is larger for middle-magnitude flows than for small and large discharges. The different contributions of interactions for various magnitude flows may be because different magnitude rainfall data could trigger different hydrological processes (Herman et al, 2013). Small discharges mainly come from base flows which are relatively stable and do not need much rainfall to be triggered, and large discharges are mainly controlled by overland flows when heavy precipitation occurs.…”
Section: Uncertainty Source Quantificationmentioning
confidence: 99%
“…ISOFLOC sensitivity analysis uses quantitative apportionment based on a variance-based sensitivity analysis. Variance based methods are widely used in hydrologic and water quality modeling studies [Wang et al, 2006;Nossent et al, 2011;Herman et al, 2013]. ISOFLOC sensitivity uses low discrepancy, quasi-random Sobol sequences to generate a sample and resample (N3d) matrix (A and B respectively) with N rows of sequences, and d columns of sensitive parameters following from the methods of Sobol' [2001] and Salteli et al [2010].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In this context, Herman et al (2013) showed that the longterm water balance is dominated by only very few parameters, irrespective of the hydrological conditions and of the model. Cuntz et al (2015) performed a global Sobol sensitivity analysis on the hydrologic model mHM.…”
Section: Parameter Sensitivities From Tedpas and Indpasmentioning
confidence: 99%
“…Guse et al (2016b) argued that the study of temporal variations in sensitivity is essential to learn about the relation between dominant parameters and governing processes under changing hydrological conditions. The characterisation of temporal dynamics of parameter sensitivity (TEDPAS) has been accomplished in diverse ways (Cloke et al, 2008;Cibin et al, 2010;Herman et al, 2013;Sanadhya et al, 2013;Guse et al, 2014;Pfannerstill et al, 2015;Pianosi and Wagener, 2016). The choice of the temporal resolution is an important factor which clearly influences the way parameters are identified and how inferences on related processes are made (Tang et al, 2007;Massmann and Holzmann, 2012;O'Loughlin et al, 2013).…”
Section: S Höllering Et Al: Regional Parameter Sensitivity To Hydromentioning
confidence: 99%
See 1 more Smart Citation